Curd-Peptide Based Novel Hydrogel Inhibits Biofilm Formation, Quorum Sensing, Swimming Mortility of Multi-Antibiotic Resistant Clinical Isolates and Accelerates Wound Healing Activity - Manna, Sounik; Ghosh, Ananta K.; Mandal, Santi M. (Frontiers in Microbiology, 2019)
The search for a bioactive natural antibacterial agent with wound healing properties is a common practice for the development of new-generation molecules. Antimicrobial peptides are a good alternative to antibiotics and easy-to-form hydrogels under self-assembled conditions without pH adjustment. With this in mind, the peptide pool was extracted from a formulated curd composed of a blend of probiotic bacteria such as Streptococcus thermophilus, Lactobacillus casei, and Bifidobacterium bifidum at an optimized ratio of 7:1:2. The water content of curd was collected by the drainage column, centrifuged, filtered through a 0.45-μM filter, and used for hydrogel preparation. Matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry (MS) analysis confirmed the presence of peptide pool in the extracted water. The prepared hydrogel was freeze dried, and its effect on biofilm formation, swarming mortality, antimicrobials, wound healing, and biocompatibility was subsequently verified. Transmission electron microscope (TEM) and scanning electron microscope (SEM) images revealed the fibrous network of peptides after self-assembly with non-polar n-hexane solvent and a porous structure after drying, respectively. The observed biocompatibility, antimicrobial activity, and strong wound healing activity of the developed curd-based hydrogel have opened a new platform for antibacterial ointment formulation.